Nayika sculptures adorning the sanctum wall of the Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
Inside the sanctum of the temple are beautiful sculptures of nayikas on the wall. Most of them are inscribed with epithets in the 10th-century kutila script. The two-armed damsel carries a chamara fly whisk.